2010
DOI: 10.1186/1477-3155-8-14
|View full text |Cite
|
Sign up to set email alerts
|

Molecular understanding of sterically controlled compound release through an engineered channel protein (FhuA)

Abstract: BackgroundRecently we reported a nanocontainer based reduction triggered release system through an engineered transmembrane channel (FhuA Δ1-160; Onaca et al., 2008). Compound fluxes within the FhuA Δ1-160 channel protein are controlled sterically through labeled lysine residues (label: 3-(2-pyridyldithio)propionic-acid-N-hydroxysuccinimide-ester). Quantifying the sterical contribution of each labeled lysine would open up an opportunity for designing compound specific drug release systems.ResultsIn total, 12 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 25 publications
(40 reference statements)
3
34
0
Order By: Relevance
“…[11] As previously found, twenty-nine lysines are present in the FhuA D1-160 with 19 lysines located on the protein surface and six inside the channel. All 29 can be labeled but only the six contained into the channel are determinant for the diffusions.…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…[11] As previously found, twenty-nine lysines are present in the FhuA D1-160 with 19 lysines located on the protein surface and six inside the channel. All 29 can be labeled but only the six contained into the channel are determinant for the diffusions.…”
Section: Resultsmentioning
confidence: 53%
“…All 29 can be labeled but only the six contained into the channel are determinant for the diffusions. [11] Through computational B-factor analysis it was found that amino acid position K556 is the least fluctuating lysine, well positioned in the smaller channel ore and most effective in flux control upon labeling. For designing a light triggered system with a precise steric control we decided to test the K556-hypothesis by generating a FhuA D1-160 variant with only one lysine in the barrel interior at position 556 and to label the lysine with NVOC-Cl.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations